A low frequency of diplexer based on Substrate Integrated Waveguide (SIW) technology with circular cavity / Nurul Nadiah Mohd Husin - Mohd Husin, Nurul Nadiah (2015)
This paper presents the prototype design of S-band diplexer using Substrate Integrated Waveguide Technology (SIW) with circular cavity. The diplexer will operate at S-band frequencies which related to the mobile tv and satellite radio application. SIW technology and circular cavity is used to design the diplexer due to its attractive advantage of reduction in size and low cost. The simulation has been performed by using CST Microwave Studio.